An inverse source identification by nonlinear optimization in a two-dimensional hyperbolic problem. Issue 12 (2nd December 2021) - Subaşı, Murat; Şendur, Faika Derya; Yaşar, Cavide
Abstract : This study deals with the identification of source function from final time state observation in a two-dimensional hyperbolic problem. The solution to the direct problem is obtained by the weak solution approach and finite element method. In the part of the inverse problem, the trust-region method and Levenberg–Marquardt method, which are nonlinear least-squares optimization methods, are used for the identification of source function. The findings are presented with numerical examples.